Antibodies to PfSEA-1 block parasite egress from RBCs and protect against malaria infection - Dipak Kumar Raj; Christian P. Nixon; Christina E. Nixon; Jeffrey D. Dvorin; Christen G. DiPetrillo; Sunthorn Pond‐Tor; Hai-Wei Wu; Grant Jolly; Lauren Pischel; Ailin Lu; Ian C. Michelow; Ling Cheng; et al. (2014)
Novel vaccines are urgently needed to reduce the burden of severe malaria. Using a differential whole-proteome screening method, we identified Plasmodium falciparum schizont egress antigen-1 (PfSEA-1), a 244-kilodalton parasite antigen expressed in schizont-infected red blood cells (RBCs). Antibodies to PfSEA-1 decreased parasite replication by arresting schizont rupture, and conditional disruption of PfSEA-1 resulted in a profound parasite replication defect. Vaccination of mice with recombinant Plasmodium berghei PbSEA-1 significantly reduced parasitemia and delayed mortality after lethal challenge with the Plasmodium berghei strain ANKA. Tanzanian children with antibodies to recombinant PfSEA-1A (rPfSEA-1A) did not experience severe malaria, and Kenyan adolescents and adults with antibodies to rPfSEA-1A had significantly lower parasite densities than individuals without these antibodies. By blocking schizont egress, PfSEA-1 may synergize with other vaccines targeting hepatocyte and RBC invasion.